PENGARUH PENAMBAHAN BEARING CAMSHAFT TERHADAP PERFORMA MESIN PADA MOTOR BENSIN 4 LANGKAH 150 CC - Muhammad Arsad Al Banjari (Jurnal Teknik Mesin dan Pembelajaran, 2020)
Abstract: This study aims to determine the effect of modification camshaft with addition needle roller bearing on the left and right side. After that compare the engine performance with the standard camshaft on the motorbike Suzuki Satria F150. The method used is an experiment. The test is carried out on the dyno test by paying attention to the value of engine speed, engine power, and the highest torque produced without limiting the gas valve opening. The results showed that after modification with the addition of a needle roller bearing the highest engine power was 18.70 HP and 12.23 N.m of torque at an engine speed of 10,888 RPM. With the addition of a needle roller bearing to the camshaft, the engine power was increased by 2.08 HP and the torque value was increased to 2 N.m Keywords: camshaft, needle roller bearing, engine performance